2002
DOI: 10.1177/0810794
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fluorosis: Variability among Different Inbred Mouse Strains

Abstract: Concurrent with the decline in dental caries has been an increase in the prevalence of dental fluorosis, a side-effect of exposure to greater than optimal levels of fluoride during amelogenesis. The mechanisms that underlie the pathogenesis of dental fluorosis are not known. We hypothesize that genetic determinants influence an individual's susceptibility or resistance to develop dental fluorosis. We tested this hypothesis using a mouse model system (continuous eruption of the incisors) where genotype, age, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 15 publications
0
95
0
15
Order By: Relevance
“…The fluoride ions are postulated to adversely affect the precipitation of hydroxyapatite that forms the enamel structure (15). Although this postulate has merit, it does not adequately explain why different inbred strains of mice had different susceptibilities/resistance to enamel fluorosis, whereas the overall levels of fluoride present in their erupted incisors did not differ significantly (16). Additionally, fluoride concentrations in enamel from unerupted human molars did not correlate positively with fluorosis severity, and it was concluded that individual genetic variation likely plays a role in fluorosis susceptibility (17).…”
mentioning
confidence: 89%
“…The fluoride ions are postulated to adversely affect the precipitation of hydroxyapatite that forms the enamel structure (15). Although this postulate has merit, it does not adequately explain why different inbred strains of mice had different susceptibilities/resistance to enamel fluorosis, whereas the overall levels of fluoride present in their erupted incisors did not differ significantly (16). Additionally, fluoride concentrations in enamel from unerupted human molars did not correlate positively with fluorosis severity, and it was concluded that individual genetic variation likely plays a role in fluorosis susceptibility (17).…”
mentioning
confidence: 89%
“…For instance, one study by Everett et al [16] showed that factors such as genetic history may affect presence of enamel fluorosis in different individuals. In their study, mice were inbred in order to create populations with similar genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the selection of these two strains is based on the fact that the strain A/J is highly susceptible to dental fluorosis, with a rapid and severe development of the disease when the animal is exposed to F, while the strain 129P3/J is less affected, with a low rate of dental fluorosis 8 . In addition, the phenotypic and genetic differences among animals, and their general availability as standard laboratory strains, have also contributed to their selection.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that certain ethnic groups are more susceptible to this disease 15,25 led some researchers to investigate the genetic susceptibility of different mice strains to dental fluorosis. It was observed that A/J mice are highly susceptible to dental fluorosis, while 129P3/J mice are little affected 8 , despite retaining more F in the body, which leads to higher femur and plasma F concentrations 5 . A recent study compared the profile of protein expression in kidney of A/J and 129P3/J mice.…”
Section: Introductionmentioning
confidence: 99%